From Authenticity to Perceived Value: Role of Souvenir Image and Place Identity on Ceramic Souvenir-Repurchasing Intention - Chen, Dong; Yaacob, Husaini Bin (South Asian Journal of Social Sciences and Humanities, 2024)
Souvenirs are regarded as an integral part of the tourist experience, serving as a tangible  reminiscence of a journey. Ceramic souvenirs of China reflect its rich cultural heritage and  therefore, tourists tend to purchase these ceramics. The present study seeks to provide empirical  evidence of the impact of authenticity and perceived value on the ceramic souvenir-repurchasing  intention of tourists in China. A survey was designed to collect data from the tourist population in  Hangzhou, China. The study focuses on the direct effects of authenticity, perceived value, along  with the mediating effect of souvenir image and the moderating role of place identity on the  ceramic souvenir-repurchasing intention. The data was analyzed through the application of SEM  and CFA for evaluation of the structural relationships among the variables. The data was  statistically analyzed, and the findings affirmed a significant impact of authenticity and perceived  value on the ceramic souvenir-repurchasing intention of the tourists. The impact of ceramic  souvenir-repurchasing intention is found to be significant on authenticity. Moreover, mediation and moderation are also proposed to be significant, showing that place identity plays an important  role in developing the purchase intention of consumers. Thus, the present study provides a valuable  understanding of tourist behavior and marketing strategies for the tourist industry.
Keywords: Authenticity; Perceived value; Souvenir image; Place identity; Ceramic souvenir repurchasing intention